(untitled) (Jurnal Adabiya, 2025)
The study aims to describe the prophetic elements in the short story Ṭabliyyah min as-Samāʾ by Yusuf Idris. This research employs a qualitative method with an interdisciplinary approach, incorporating the concepts of prophethood and literature. The concept of prophethood in this study serves as an analytical tool to uncover the prophetic elements present in literary works. The findings indicate that Ṭabliyyah min as-Samāʾ by Yusuf Idris contains the concept of prophetic ethics, which includes humanization, liberation, and transcendence. In addition to these prophetic aspects, the short story also encompasses elements of dehumanization that contradict prophetic ethics. The study concludes that Ṭabliyyah min as-Samāʾ by Yusuf Idris embodies the aspect of humanization in the form of maintaining brotherhood. Liberation is reflected through the struggle against economic injustice, while transcendence is demonstrated through the attitude of fear and obedience toward religious obligations as a Muslim. Furthermore, the element of dehumanization is evident in behaviors that disregard respect for fellow human beings. Penelitian bertujuan untuk mendeskripsikan bagaimana benrtuk muatan profetik dalam cerpen Ṭabliyyah min as-Samāʾ karya Yusuf Idris. Metode penelitian bersifat kualitatif dengan menggunakan pendekatan interdisipliner yang meliputi konsep kenabian dan konsep sastra. Konsep kanabian dalam penelitian ini digunakan sebagai alat untuk mengungkpa bagaimana bentuk muatan profetik yang terdapat dalam karya sastra. Hasil penelitian ini menunjukan bahwa cepren Ṭabliyyah min as-Samāʾ karya Yusuf Idris memuat konsep etika profetik yang meliputi humanisasi, liberasi dan transdensi. Selain konsep profetik tersebut cerpen ini juga mengandung aspek dehumanisasi yang berlawanan dengan etika profetik. Kesimpulan dari penelitian ini adalah, cerpen Ṭabliyyah min as-Samāʾ karya Yusuf Idris mengandung aspek humanisasi dalam bentuk menjaga persaudaraan. Liberasi yang di tunjukan melalui pembebasan dari ketidakadilan ekonomi. Aspek transdensi yang ditunjukan melalui sikap takut dan taat terhadap segala kewajiban sebagai seorang muslim. Adapun aspek dehumanisasi yang ditunjukan berupa sikap tidak menghormati sesama manusia.